Implementasi Pembelajaran Pendidikan Agama Islam Materi Kisah Teladan Nabi Muhammad Dengan Menggunakan Video Animasi Pada Siswa Kelas V Sd Negeri 15 Kepahiang - Fauziah Silaturrahmi; Ali Akbarjono; Ahmad Syarifin (JPT : Jurnal Pendidikan Tematik, 2024)
This study aims to determine the implementation of Islamic Religious Education learning material The Story of the Prophet Muhammad by using animated videos in fifth grade students of SD Negeri 15 Kepahiang, as well as knowing the supporting and inhibiting factors. This research belongs to the type of qualitative research. The data collection technique used is direct observation by observing the learning process of Islamic Religious Education material on the Example of the Prophet Muhammad by using animated videos. Then direct interviews with the Principal and PAI teachers concerned, then documentation. The results of the study indicate that the implementation of Islamic Religious Education learning material The Story of the Prophet Muhammad by using animated videos has a positive impact on students. In practice, the teacher shows animated videos through several stages, namely preparation, implementation, and follow-up. The animated videos used in learning are adjusted to the learning objectives, and the teacher communicates the activities carried out with the students, and there is a folow-up in the form of giving assignments from the teacher as material reinforcement. Supporting and inhibiting factors that influence, namely from the aspect of students, namely the understanding of students who are different, then from the aspect of teachers, namely, the ability of teachers to operate computers, and aspects of facilities infrastructure.